β-lactoglobulin and lactoferrin complex coacervates: Characterization and putative applications as encapsulation device - Tavares, Guilherme Miranda (2015)
Encapsulation of bioactives has been used by the food industries for decades and represents a great potential for the development of innovative products. Given their versatile functional properties, milk proteins in particular from whey have been used for encapsulation purposes using several encapsulation techniques. In parallel, recent studies showed the ability of oppositely charged food proteins to co-assemble into microspheres through complex coacervation. Understanding the driving forces governing heteroprotein coacervation process and how it is affected by the presence of ligands (bioactives) is a prerequisite to use heteroprotein coacervates as encapsulation device. In this context, the objective of my thesis work was to understand the mechanism of complex coacervation between β-lactoglobulin (β-LG) and lactoferrin (LF) in the absence and presence of small ligands. The conditions of optimal β-LG - LF coacervation were found at pH range 5.4-6 with a molar excess of β-LG. Remarkably, LF showed selective coacervation with β-LG A, the slightly more negative isoform. At molecular level, the presence of two binding sites on LF for β-LG was evidenced. Moreover, the heterocomplexes such as pentamers LF(β-LG 2 ) 2 and quite large complexes (LFβ-LG 2 )n were identified as the constituent molecular species of the coacervate phase. To evaluate the β-LG - LF complex coacervation in the presence of small ligands, models of hydrophobic (ANS) and hydrophilic molecules (folic acid) were used. Although under the experimental conditions tested the small ligands did not interact with β-LG, both interacted with LF inducing its self- association into nanoparticles. High relative concentrations of small ligands affected the interaction between the two proteins leading to a transition from coacervation to aggregation regime.